NUMERICAL METHODS FOR APPROXIMATING EIGENVALUES OF BOUNDARY VALUE PROBLEMS - Usmani, Kiaz A.; Isa, Mohammad (International Journal of Mathematics and Mathematical Sciences, 1986)
This paper describes some new finite difference methods for the approximation of eigenvalues of a two point boundary value problem associated with a fourth order linear differential equation of the type (py＂)＂- (q y')' + (r - λs)y =0. The smallest positive eigenvalue of some typical eigensystems is computed to demonstrate the practical usefulness of the numerical techniques developed.